An Evolutionarily Conserved Coreceptor Gene Is Essential for CLAVATA Signaling in Marchantia polymorpha - Takahashi, Go; Betsuyaku, Shigeyuki; Okuzumi, Natsuki; Kiyosue, Tomohiro; Hirakawa, Yuki (Frontiers in Plant Science, 2021)
Growth and development of land plants are controlled by CLAVATA3/EMBRYO SURROUNDING REGION-related (CLE) family of peptide hormones. In contrast to the genetic diversity of CLE family in flowering plants, the liverwort Marchantia polymorpha possesses a minimal set of CLE, MpCLE1(TDIF homolog) and MpCLE2 (CLV3 homolog). MpCLE1 and MpCLE2 peptides exert distinct function at the apical meristem of M. polymorpha gametophyte via specific receptors, MpTDIF RECEPTOR (MpTDR) and MpCLAVATA1 (MpCLV1), respectively, both belonging to the subclass XI of leucine-rich repeat receptor-like kinases (LRR-RLKs). Biochemical and genetic studies in Arabidopsis have shown that TDR/PXY family and CLV1/BAM family recognize the CLE peptide ligand in a heterodimeric complex with a member of subclass-II coreceptors. Here we show that three LRR-RLK genes of M. polymorpha are classified into subclass II, representing three distinct subgroups evolutionarily conserved in land plants. To address the involvement of subclass-II coreceptors in M. polymorpha CLE signaling, we performed molecular genetic analysis on one of them, MpCLAVATA3 INSENSITIVE RECEPTOR KINASE (MpCIK). Two knockout alleles for MpCIK formed narrow apical meristems marked by promMpYUC2:GUS marker, which were not expanded by MpCLE2 peptide treatment, phenocopying Mpclv1. Loss of sensitivity to MpCLE2 peptide was also observed in gemma cup formation in both Mpclv1 and Mpcik. Biochemical analysis using a Nicotiana benthamiana transient expression system revealed weak association between MpCIK and MpCLV1, as well as MpCIK and MpTDR. While MpCIK may also participate in MpCLE1 signaling, our data show that the conserved CLV3-CLV1-CIK module functions in M. polymorpha, controlling meristem activity for development and organ formation for asexual reproduction.